The new normal of remote work: exploring individual and organizational factors affecting work-related outcomes and well-being in academia - Capone, Vincenza; Schettino, Giovanni; Marino, Leda; Camerlingo, Carla; Smith, Alessandro; Depolo, Marco (Frontiers in Psychology, 2024)
Background Flexible work arrangements have become increasingly popular, driven by the widespread adoption of digital technologies in the workplace because of the pandemic. However, there is a scarcity of studies concerning remote work, especially related to technical-administrative staff (TAS) in academia. Therefore, the current study, adopting the Job Demands-Resources model, aimed to investigate the relationships between remote working self-efficacy, organizational support, techno-complexity, mental well-being, and job performance among TAS during remote working. Methods A total of 373 individuals from TAS of a large Italian university participated in this study by completing a self-report questionnaire. Results The findings showed positive and significant relationships between remote self-efficacy and job satisfaction as well as between such a perceived efficacy and mental well-being. Perceived support from supervisors acted as a protective factor against techno-complexity. In contrast, perceived support from colleagues emerged as able to promote well-being and job satisfaction. In addition, the latter was positively associated with well-being. Finally, individual job performance was positively affected by job satisfaction and negatively by techno-complexity. Conclusion This study highlights the need for interventions to support TAS in remote working environments by leveraging employees’ self-efficacy as a key factor in reducing stress related to new technologies as well as enhancing well-being, job satisfaction, and, in turn, their performance.